Старовинні парки – першоджерела інтродукції тропічних і субтропічних рослин в Україні - Cherevchenko, T.M.; Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Possible primary sources of tropical and subtropical plants introduction into Ukraine through old gardens-parks of the 18–19th cc. are cited. The species content of plants growing in greenhouses of old parks of Ukrainian and Polish magnates residences in Eastern Europe (now the territory of Ukraine) has been analysed.